Pengaruh Kemandirian Fiskal dan Efektivitas Pengelolaan Anggaran Terhadap Alokasi Belanja Modal pada Kabupaten/Kota di Provinsi Sumatera Barat - Surya Ramadhani; Nelly Masnila; Yevi Dwitayanti (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to analyze the effect of fiscal independence and budget management effectiveness on capital expenditure allocation in districts/cities in West Sumatra Province. Analysis of aid data was conducted using multiple linear regression with SPSS software version 29. The data used are secondary data, collected through documentation, such as books, regulations, and other sources relevant to regional financial performance, including the fiscal independence ratio, budget management effectiveness, and capital expenditure, as well as data from related agencies. The results of the study indicate that budget management effectiveness has a significant positive effect on capital expenditure allocation, while fiscal independence has no significant effect. This finding emphasizes the importance of improving budget management to increase public investment in the region. The implications of this study are important for local governments and policy makers in formulating strategies to improve public welfare by increasing capital expenditure allocation.